2010
DOI: 10.3171/2010.5.jns091277
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic lesions for the treatment of psychiatric disorders

Abstract: Object. The use of deep brain stimulation (DBS) has recently been expanded to the investigational treatment of specific psychiatric disorders. Much like movement disorders, the targets selected for DBS are based on past experience with stereotactic lesions. A literature review of past studies incorporating stereotactic lesions for psychiatric disorders was performed to provide historical context and possible guidance for current and future attempts at treating psychiatric disorders with DBS.Methods. Original c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 33 publications
1
48
0
1
Order By: Relevance
“…More than three thirds believe that they are a valid alternative to DBS for some patients, but also almost half of the experts expect that soon there won't be experts who master lesion procedures. Also in the literature there is support to keep lesion procedures as an important alternative for appropriately selected patients both for movement disorders (e.g., Parkinson's disease; Bronstein et al 2011) and psychiatric disorders (Leiphart and Valone 2010) like OCD or anorexia nervosa (Barbier et al 2011;D'Astous et al 2013;Greenberg et al 2010;Kondziolka et al 2011). In particular, an international expert panel has recently stated in a consensus paper that "until scientifically proven otherwise, DBS is not superior to ablative surgery for psychiatric disorders" (Nuttin et al 2014).…”
Section: Patient-related Dimensionmentioning
confidence: 99%
“…More than three thirds believe that they are a valid alternative to DBS for some patients, but also almost half of the experts expect that soon there won't be experts who master lesion procedures. Also in the literature there is support to keep lesion procedures as an important alternative for appropriately selected patients both for movement disorders (e.g., Parkinson's disease; Bronstein et al 2011) and psychiatric disorders (Leiphart and Valone 2010) like OCD or anorexia nervosa (Barbier et al 2011;D'Astous et al 2013;Greenberg et al 2010;Kondziolka et al 2011). In particular, an international expert panel has recently stated in a consensus paper that "until scientifically proven otherwise, DBS is not superior to ablative surgery for psychiatric disorders" (Nuttin et al 2014).…”
Section: Patient-related Dimensionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that more than 170 individuals have been treated with ablative procedures (mainly cingulotomy and callosotomy, respectively). The clinical benefit in schizophrenia however lagged markedly behind the success achieved by DBS in other psychiatric disorders (Leiphart & Valone, 2010). Thus, no valid expertise regarding putative anatomical targets in schizophrenia can be drawn from previous neurosurgical approaches.…”
Section: First Approach: Functional Lesioningmentioning
confidence: 99%
“…Review of the uncontrolled studies suggests that at least 50-60% of the patients show a response to surgery [112]. A recent review [113] suggests that capsulotomy may be a more effective procedure for OCD. There may be some rare serious adverse effects including intracerebral hemorrhage, infection, postoperative convulsions and so on which are more commonly seen with open surgeries.…”
Section: Neurosurgerymentioning
confidence: 99%